Pengaruh Persepsi Masyarakat Tentang Perencanaan Partisipatif Terhadap Sikap Untuk Berpartisipasi: Kasus Penyusunan Rtbl Kawasan Tambaklorok Kota Semarang - Safilia Vinandita; Holi Bina Wijaya (Teknik PWK (Perencanaan Wilayah Kota), 2017)
Social factors influence attitude towards participation. This paper examines the influence of social factor especially citizen perception about participatory planning on attitudes toward participation in the preparation of buildings and environments planning (RTBL) Tambaklorok. Citizens perception about planning is shaped by attention, learning, memory and expectation. This perception shapes individual’s attitude that includes receiving, responding, valuing, and responsibility. The study shows that citizens have lack of attention to planning information and responsibilities. But generally they have positive thought. There is a directly proportional relationship between the two variables, namely the perceptions and attitudes. Better perception of planning, leads to the better attitude towards the implementation of the plan. In addition, there is a difference between two groups with different levels of education. Based on this, good attitudes are shaped by enhancing public mindset, so improving community awareness and understandings are needed through the information sharing and education improvement with effective methods.